PENDEKATAN SISTEM 2D MODEL STREETER-PHELPS UNTUK MODEL POLUSI SUNGAI - MATAKUPAN, RUDY WOLTER (PATTIMURA UNIVERSITY, 2011)
Applications to positive 2D system can follow Steeter-Phelps model to river flow model. bymodifying the discrete values. mathematical model structure provided by the river flow at timestep t is proportional to the length of rivers and water velocity. The variables that influence isDissolved oxygen (DO) and Biological oxygen demand (BOD), both these variables arecalculated by balance considerations equetion with the screening process, the process ofreaeration, and the source of BOD established a mathematical model of positive 2D systems